International Humanitarian Law Review on Genetically Modified Super Soldier - Asmi, Nur (Faculty of Law, Khairun University, 2017)
This research aims to find out and understand genetically modified super soldier as well to find out and understand whether genetically modified super soldier is legitimate under international humanitarian law.This paper used normative legal approach by utilizing literature study. Data collected are secondary data derived from conventions, books, research, scientific journal and other written sources relevant. Data collected was analyzed descriptively.The result inflicted of this research as follows: 1) Genetically modified super soldier is genome manipulation on soldier aimed to modify sequencing or gen characteristic to create stronger soldiers by utilizing biotechnology, pharmacology, neuroscience, nanotechnology, and biochemical. 2) Genetically modified super soldier collides ethical and human rights as it did not consider informed consent of soldier. Genetically modified super soldier requires law review in its justification as means and method of warfare because some of genetically modified super soldier technologies constitute possibilities in disobeying international humanitarian law principles, and its justification of means and method of warfare that did not comply ethical requirement.